Early Childhood Teacher Assessment and Competence: A Systematic Review Analysis - Izzati, Khoerul; Hayati, Nur (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Competence of early childhood education teachers will be able to enhance early childhood development according to their needs and basic principles. Children who develop well will become a superior generation in the future. This study explores research trends and patterns in early childhood education, focusing on the competencies that early childhood teachers must possess. A systematic literature review (SLR) was the methodology used. Data was collected from the Scopus database using keywords such as Early Childhood, Education, Teachers, Competence, and Assessment. Over a 50-year period from 1975 to 2025, 664 research articles were identified, with 460 meeting the analysis criteria. Of these, 15 articles were selected for detailed analysis based on inclusion and exclusion criteria. The findings show a fluctuating trend in the number of articles published each year, reflecting the changing relevance and focus of teacher competencies in the early childhood education sector. The main topics of the SLR include children, early childhood teacher competencies, early childhood teacher assessment, and early childhood development. The data demonstrate the importance of preparing competent early childhood teachers before they begin teaching in schools. These competencies include leadership, professional, social, and problem-solving skills. Furthermore, various training programs can improve the quality of early childhood education (PAUD) teachers and keep up with evolving trends. This study provides a comprehensive overview of research trends in PAUD teacher competencies.